Mechanical and Durability Properties of Lightweight Foamed Concrete Containing Palm Kernel Shell - Awang, Hanizam; Adeshina Dauda, Adebayo; Arminda, Wenny (International Journal of Engineering and Technology, 2018)
The research project aimed to investigate the effect of palm kernel shell (PKS) on the mechanical strength and durability of foamed concrete at the level of 10% to 60%. The samples were designed and prepared having a dry density of 1600 kg/m3with a binder to filler ratio of 1:1.2. Hardened foamed concrete samples were subjected to air cured and tested at the age of 7, 14, 28, 56 and 90 days. Mechanical performance of the PKS foamed concrete was assessed in term of its compressive strength. Durability properties namely water absorption and vacuum porosity were investigated. The result shows that the addition of PKS to lightweight foamed concrete up to 30% significantly improve the mechanical properties and the durability of the foamed concrete.Â Â